Microcirculatory Response to Blood vs. Crystalloid Cardioplegia During Coronary Artery Bypass Grafting With Cardiopulmonary Bypass - Aykut, Güclü; Ulugöl, Halim; Aksu, Uğur; Akin, Sakir; Karabulut, Hasan; Alhan, Cem; Toraman, Fevzi; Ince, Can (Frontiers in Medicine, 2022)
ABSTRACT Background: Blood cardioplegia attenuates cardiopulmonary bypass (CPB) induced systemic inflammatory response in patients undergoing cardiac surgery. This may favourably influence the microcirculation since the systemic inflammatory response is an important cause of microcirculatory alterations in this cohort. The aim of this study was to investigate whether blood cardioplegia would offer advantages over crystalloid cardioplegia in the preservation of microcirculation in patients undergoing coronary artery bypass grafting (CABG) with CPB. Methods: In this prospective observational study, 20 patients who received crystalloid (n=10) or blood cardioplegia (n=10) were included. The microcirculatory measurements were obtained sublingually using incident dark-field imaging at 5 time points ranging from the induction of anaesthesia (T0) to discontinuation of CPB (T5). Results: In both crystalloid (CCG) and blood cardioplegia (BCG) groups, perfused vessel density (PVD), total vessel density (TVD) and proportion of perfused vessels (PPV) were reduced after the beginning of CPB. The observed reduction in microcirculatory parameters during CPB was only restored in patients who received cold blood cardioplegia and increased to baseline levels as demonstrated by the percentage changes (%Δ) in all functional microcirculatory parameters from T0 to T5 [%ΔTVDT0-T5(CCG): -10.86±2.323 vs. %ΔTVDT0-T5(BCG): 0.0804±1.107, p<0.001; %ΔPVDT0-T5(CCG): -12.91±2.884 vs. %ΔPVDT0-T5(BCG): 1.528±1.144, p<0.001; %ΔPPVT0-T5(CCG): -2.345±1.049 vs. %ΔPPVT0-T5(BCG): 1.482±0.576, p<0.01]. Conclusions: Blood cardioplegia ameliorates CPB induced microcirculatory alterations in CABG patients better than crystalloid cardioplegia, which may reﬂect attenuation of the systemic inﬂammatory response. Future investigations are needed to identify the underlying mechanisms of the beneficial effects of cold blood cardioplegia on microcirculation.